Nonlinear seismic responses of the powerhouse of a hydropower station under near-fault plane P-wave oblique incidence. (15th November 2019) - Song, Zhiqiang; Wang, Fei; Li, Yanlong; Liu, Yunhe
Highlights: The structural response under near-fault plane P-wave oblique incidence was studied. The displacement equation of free surface and analytical solution are derived. The oblique input method on the basis of viscoelastic artificial boundary is derived. The powerhouse has stronger damage under oblique input of pulse-like ground motion. Abstract: Near-fault ground motion has unique motion characteristics that are mainly manifested as long periodic velocity and large displacement pulses. Engineering structures in near-fault areas are frequently damaged severely. Most previous studies have assumed that the seismic waves on a site in a near-fault area are vertical or approximately vertical incidence that are prone to large oblique incidence angles. First, the displacement expression of free surface is derived on the basis of the boundary conditions of free surface. The theoretical displacement curves of free surface in the range of 0°–90° are drawn on the basis of displacement expression. Then, the most unfavorable incidence angle (65°) is obtained. Subsequently, the equivalent nodal force formula on the artificial boundary node of plane P-wave oblique incidence is derived on the basis of the dynamic viscoelastic artificial boundary. Numerical verification shows that the proposed method has good precision. Ten near-fault ground motions are selected from the strong earthquake database of the Pacific Earthquake Engineering Research Center (PEER), in which velocity and non-velocity pulse ground motions have five groups each. Finally, the nonlinear seismic responses of the ground powerhouse of a hydropower station are investigated when the incidence angles of a near-fault plane P-wave are 15°, 30°, and 65°. Results show that the damage of the powerhouse under pulse-like ground motions are more serious than that under non-pulse ground motions when the incidence angles of seismic wave are the same. The superstructural interlayer displacement angles of the powerhouse and the relative displacements in the water flow direction between the upstream and downstream cattle legs increase with the ratio of the peak ground velocity to the peak ground acceleration (PGV/PGA). In comparison with the smaller incidence angle of seismic wave, the PGV/PGA of ground motion has a more significant influence on the seismic response of the powerhouse at a larger incidence angle of seismic wave.